2020
DOI: 10.15728/bbr.2020.17.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Market Reaction to the Issuance of Capital Instruments by Brazilian Banks

Abstract: Banks are allowed to employ debt instruments in order to meet the minimum requirements of capital, as long as they comply with the subordination agreements as determined by the Basel Accords. This paper takes account of the effective powers of these instruments, viewed from the standpoint of the investors, and seeks to assess their impact on the return on investments in the shares of the issuing banks within Brazil's capital markets. The article is, to a large extent, based on the research findings of Ammann e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…Pereira and Tavares (2021) stated that there are several factors that support and show that DTA can demonstrate information about the quality of earnings and, in their studies, they showed that, for company-years with large differences in DTA, it is less persistent in future profits than for firm-years with small DTA differences. Zanon and Dantas (2020) showed in their studies that companies with a high volume (low volume) of DTA stock have a large Contextus -Contemporary Journal of Economics and Management (2024), 22, e91530 | (small) effect on earnings persistence and can be used as a proxy for earnings quality.…”
Section: Dta and Development Of Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…Pereira and Tavares (2021) stated that there are several factors that support and show that DTA can demonstrate information about the quality of earnings and, in their studies, they showed that, for company-years with large differences in DTA, it is less persistent in future profits than for firm-years with small DTA differences. Zanon and Dantas (2020) showed in their studies that companies with a high volume (low volume) of DTA stock have a large Contextus -Contemporary Journal of Economics and Management (2024), 22, e91530 | (small) effect on earnings persistence and can be used as a proxy for earnings quality.…”
Section: Dta and Development Of Hypothesesmentioning
confidence: 99%
“…DTA become the most common means of smoothing bank profits after the launch of Accounting Pronouncement Committee No. 32 (CPC 32), as it requires companies to evaluate at fair values, both assets and total liabilities in the Balance Sheet (Zanon & Dantas, 2020). Beatty and Liao (2014) used the DTA model to measure banks' earnings smoothing.…”
Section: Dta and Development Of Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations